Main Paradigms of the Concept of Evil in Western Anthropological and Psychological Studies - Popov, V. Y.; Popova, E. V. (Anthropological Measurements of Philosophical Research, 2024)
Purpose. The authors aim to investigate the evolution of the paradigm shift of the concept of evil in Western philosophical and psychological thought. Theoretical basis is determined by the latest methodological approaches in studying the relationship between philosophical, psychological, and theological approaches to understanding the essence of evil and its manifestations. Originality. For the first time in Ukrainian philosophical literature, a systematization of the evolution of the concept of evil in the philosophical and psychological sciences has been carried out. Conclusions. Analyzing the main mythological, theological, philosophical, and psychological concepts of evil provides an opportunity to systematize them through the main five paradigms. The primordial paradigm can be considered dualistic, which retains its influence until our time. Evil is understood in it as the personification of natural disasters, diseases, human crimes, and a force opposing Good. Ancient philosophy and Christianity try to deprive evil of its ontological status: evil does not exist as such but is only a lack of Good. Based on this understanding, a privative paradigm was formed, which dominated the European philosophical and theological consciousness for more than a millennium. It became the basis for philosophical theodicy: the justification of the all-good God in the face of clearly existing evil. But at the end of the 18th century, it gave way to the dialectical-romantic paradigm, the most vivid representatives of which are Schelling, Hegel, and Nietzsche. The concept of evil is reinterpreted and considered as a necessary component of the world, which, along with good, belongs to a higher reality. The concept of evil receives a new understanding in the psychoanalysis of Freud, Jung, and Fromm: its source is determined by the human subconscious, and its external manifestation is aggression. A similar understanding of evil is inherent in many other psychological schools, some of which also conducted psychological experiments on the originally evil nature of man. However, such "experiments" are characteristic of the social practices of totalitarian regimes, based on which the concept of the "banality" of evil arises. The appearance of the latest postmodern paradigm of understanding evil is connected with the attempt of some thinkers to reject all previous concepts of evil and a kind of return to the oldest dualistic paradigm. It would seem that the fall of most totalitarian regimes and the expectation of the "end of history" did not give grounds for popularizing this paradigm. Still, the events of the early 20s of our century indicate the need for its actualization.